Delayed Development of Aneurysmal Dilatations in Patients with Extracranial Carotid Artery Dissections. (December 2022) - van Laarhoven, Constance J.H.C.M.; Arnold, Marcel; Danilova, Maria; Dreval, Marina; Ferrari, Elena; Simonetti, Barbara G.; Gralla, Jan; Heldner, Mirjam; Kalashnikova, Ludmila; Mancuso, Michelangelo; Metso, Tiina M.; Steinsiepe, Valentin K.; et al.
Abstract : Objective: Dissection of the carotid artery (CaAD) may result in aneurysm formation. The present study was undertaken to evaluate the time of onset of post-dissection extracranial carotid artery aneurysms (ECAA) following CaAD, and to analyse independent risk factors for the development of these aneurysms. Methods: From four European stroke centres, 360 patients with extracranial CaAD were included. The time between the estimated dissection onset and aneurysm formation was analysed, and the clinical risk factors increasing the probability of aneurysm were assessed. Results: The median duration of follow up was 5.2 months (range 0 – 24 months). A total of 75 post-dissection ECAAs were identified in 70 patients (19.4%, 95% confidence interval [CI] 15.7 – 23.8). In 52 of 70 (74%) patients, the ECAA was diagnosed at the initial clinical work up of CaAD diagnosis, with the median estimated time of dissection onset to ECAA diagnosis being six days (interquartile range [IQR] 0 – 25). In the remaining 18 (26%) patients who had normal carotid arteries at the initial imaging, the aneurysm diagnosis was made a median of 6.2 months (189 days) from the original imaging (IQR 128 – 198). A Cox proportional hazards model showed that both multiple artery dissections (hazard ratio [HR] 2.58, 95% CI 1.54 – 4.33) and arterial tortuosity (HR 1.79, 95% CI 1.08 – 2.95) were associated with presence of ipsilateral ECAA. Conclusion: This post hoc cohort analysis showed substantially delayed development of ipsilateral ECAA in patients with CaAD, months after baseline. Multiple dissections and arterial tortuosity are associated with the presence of ECAA and can be used in future prediction models of ECAA development in patients with CaAD.